Bioethics and the Psychosphere - Sgreccia, Elio (Medicina e Morale, 2024)
Bioethicshas so far considered, at least in a direct and prevalent sense, interventions in the biological and medical fields: from genetic engineering to the problems of euthanasia and ecology, the landscape of bioethics reflections has unfolded and is unfolding to reaffirm values, to enucleate criteria and performulate norms of behavior